Treating alcohol use disorders in primary care - a qualitative evaluation of a new innovation: the 15-method - Sara Wallhed Finn; Anders Hammarberg; Sven Andreasson; Maria Jirwe (Taylor & Francis Group, 2021)
Objective This study aims to explore how the characteristics of an innovation, the 15-method, a stepped care model for treatment of alcohol use disorders in primary care was perceived. Methods/Design/Setting/Subject General practitioners and heads of primary care units (n = 10) that delivered the 15-method in a randomized controlled trial participated in individual interviews at two occasions in Stockholm, Sweden. Data were analyzed with theoretical thematic analysis, using Diffusion of Innovation Theory. Results The participants described that offering the 15-method met a need among their patients. Participants were positive towards the training and the manual for the method. They mentioned a previous lack of routines to work with alcohol use disorders. The 15-method was described as easy to use. It would however be more feasible to implement in a team of different professions, rather than among general practitioners only. Priorities made by regional health care managers were described as important for the implementation, as well as financial incentives. A barrier to implementation was that alcohol screening was perceived as difficult. While the 15-method was perceived as effective in reducing the patients' alcohol use and cost effective, participants expressed uncertainty about the long-term effects. Conclusions The 15-method provides structure for treatment of alcohol use disorders and is described by general practitioners and heads as a promising approach. Being able to offer treatment for alcohol dependence may increase the uptake of alcohol interventions in primary care.KEY POINTS Little attention has been given to develop treatment models for alcohol use disorders that are adapted to primary care settings. This study describes how an innovation, the 15-method, a stepped care model for treatment of alcohol use disorders in primary care was perceived. The 15-method provides structure for treatment of alcohol use disorders in primary care and is described by general practitioners and heads as a promising approach. Being able to offer treatment for alcohol dependence may increase the uptake of alcohol interventions in primary care.